2005
DOI: 10.1164/rccm.200406-763oc
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Cognitive, Emotional, and Quality-of-Life Outcomes in Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS) has a high mortality and is associated with significant morbidity. Prior outcome studies have focused predominant on short-term outcomes (6-12 months). We assessed longitudinal neurocognitive, emotional, and quality of life in ARDS survivors at hospital discharge, and 1 and 2 years after hospital discharge using neuropsychologic tests and emotional and quality-of-life questionnaires. Neurocognitive sequelae occurred in 73% (54 of 74) of ARDS survivors at hospital disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
440
4
15

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 680 publications
(518 citation statements)
references
References 59 publications
36
440
4
15
Order By: Relevance
“…Risk factors for depression at 1 year are alcohol dependence, female gender and younger age; risk factors for developing anxiety are lower Pa o 2 /Fi o 2 ratio and duration of mechanical ventilation 33. Cognitive impairment with reduced memory, attention and task execution is also common 34. Such morbidity has a significant economic burden and the development of physical and psychological rehabilitation strategies are important to improve outcome in ARDS/ALI survivors.…”
Section: Epidemiologymentioning
confidence: 99%
“…Risk factors for depression at 1 year are alcohol dependence, female gender and younger age; risk factors for developing anxiety are lower Pa o 2 /Fi o 2 ratio and duration of mechanical ventilation 33. Cognitive impairment with reduced memory, attention and task execution is also common 34. Such morbidity has a significant economic burden and the development of physical and psychological rehabilitation strategies are important to improve outcome in ARDS/ALI survivors.…”
Section: Epidemiologymentioning
confidence: 99%
“…While low V T strategies have been embraced, recent work indicates that survival from ARDS may be complicated by neurocognitive decline correlated to hypoxaemic periods during mechanical ventilation [23,24]. Richard et al [25] advocate recruitment manoeuvres or increasing PEEP as alternative strategies to counteract low V T derecruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ARDS survivors suggest that a combination of acute hypoxia, hypoperfusion, and hyperglycemia plays an important role in the long-term cognitive sequelae of critical illness [3,58,59]. However, it has been difficult to demonstrate a clear relationship, given the lengthy interval between stimulus and effect and the great number of additional contributing variables that can obscure downstream effects.…”
Section: Occult Diffuse Brain Injurymentioning
confidence: 99%
“…However, it has been difficult to demonstrate a clear relationship, given the lengthy interval between stimulus and effect and the great number of additional contributing variables that can obscure downstream effects. Among ARDS survivors, Hopkins and colleagues showed that the degree of CD at 1 year is significantly correlated with the durations of hypoxia [58] and mean arterial blood pressure less than 50 mmHg during the ICU stay [3]. In animals, hyperglycemia markedly enhances hypoxic-ischemic brain damage due to increased brain edema and disrupted cerebral metabolism [60].…”
Section: Occult Diffuse Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation